2019
DOI: 10.1111/ijfs.14158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotic L. plantarum 299v on consumer quality, accumulation of phenolics, antioxidant capacity and biochemical changes in legume sprouts

Abstract: This study evaluated the influence of Lactobacillus plantarum 299v on the consumer quality of legume sprouts. The probiotic‐rich sprouts were produced by soaking the seeds in probiotic water suspension and further sprouting at 25 °C for 4 days. The enrichment of the sprouts with L. plantarum 299v only slightly affected the sensory quality ‐ the overall acceptability of the probiotic‐rich sprouts was usually higher. The probiotic‐rich sprouts exhibited increased activity of polyphenol oxidase (the highest activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The application of yeasts on sprouts is very intriguing, in light of probiotic benefits that may occur together with the elicitation effects [117][118][119].…”
Section: Delving Into Elicitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of yeasts on sprouts is very intriguing, in light of probiotic benefits that may occur together with the elicitation effects [117][118][119].…”
Section: Delving Into Elicitorsmentioning
confidence: 99%
“…However, to date, elicitors have been generally investigated alone and not in combination, thereby precluding observations about possible additive and synergistic effects that could result from versatile and flexible application of variable conditions and parameters (e.g., type, dose, and application method of abiotic and/or biotic factors). [119] Seeds soaked in distilled water or probiotic water suspension (1 × 10 6 CFU per 1 g of seeds) of Saccharomyces cerevisiae var. boulardii seedlings sprayed daily with 5 mL of Milli-Q water or 5 mL of probiotic water suspension on 1st day of cultivation (1 × 10 6 CFU per 1 g of seeds)…”
Section: Delving Into Elicitorsmentioning
confidence: 99%
“…As for starch content, the probiotic‐enrichment process did not change the total starch content of the sprouts, but it increased the portion of RS (from 4.0% to 8.4%) (Świeca, Gawlik‐Dziki, et al., 2019). In another study, the sensory evaluation suggested that the L. plantarum ‐rich sprouts exerted higher overall acceptability than the normal sprouts (Złotek et al., 2019). In addition, the L. plantarum ‐enrichment process increased the content of polyphenol oxidase and α‐amylase and decreased the content of protease, which may affect the metabolism of the stored materials (e.g., starch and protein) and modify the bioavailability of phenolics (Złotek et al., 2019).…”
Section: Applications Of Adzuki Bean and Its Componentsmentioning
confidence: 99%
“…However, the contents of starch and protein decreased, probably owing to the uptake of the yeast (Świeca, Kordowska‐Wiater, et al., 2019). Alternatively, adzuki bean seeds could be soaked in the water suspended with L. plantarum 299v (1 × 10 8 colony‐forming unit per 1 g of seeds) for 6−8 h, followed by a germination process at 25°C (Świeca, Gawlik‐Dziki, et al., 2019; Świeca et al., 2020; Złotek et al., 2019). The digestibility of the L. plantarum ‐rich sprout protein (83.4%) was higher than that of normal sprout protein (75.7%) (Świeca, Gawlik‐Dziki, et al., 2019).…”
Section: Applications Of Adzuki Bean and Its Componentsmentioning
confidence: 99%
“…Recently, some alternative approaches were been applied, e.g., the use of natural phenolic-rich solutions to improve the phenolic content and antioxidant capacity in stored mung bean sprouts and shredded iceberg lettuce [ 25 , 26 ]. Additionally, functional coatings [ 27 ] or enrichment with probiotics [ 9 , 28 ] turned out to be effective “tools”.…”
mentioning
confidence: 99%